2023
DOI: 10.3390/microorganisms11041063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of Haemogregarine Hemoparasites (Apicomplexa: Adeleorina: Haemogregarinidae) in Populations of Native and Introduced Pond Turtles in Eastern Europe

Abstract: Haemogregarines (Apicomplexa: Adeleorina) are the most common and widespread reptilian blood parasites. Haemogregarina stepanowi was the first haemogregarine described from a reptile, the European pond turtle Emys orbicularis, and initial assessments indicated it was widespread across different pond turtle host species across much of Europe, the Middle East and North Africa. However, recent molecular assessments have indicated the presence of multiple genetically distinct forms in North Africa and the Iberian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…While levels of COI genetic variations clearly indicate the occurrence of several haemogregarine species within the same host species in sympatry, even in syntopy, which is illustrated by numerous cases of coinfections, it is still extremely difficult to link a particular molecular lineage to a specific morphological species, as also reported in [ 17 ]. While the first molecular investigations on Haemogregarina have shown from nuclear markers that H. stepanowi possesses a wide distribution though Europe, Turkey, and the Middle East to Iran with a very low host-specificity [ 12 ], the most recent advents in molecular systematics of H. stepanowi have shown that this species could be actually split into a great number of distinct cryptic haemogregarine species [ 15 , 19 , 52 , 53 ], infecting E. orbicularis and M. leprosa on the one hand and additional hosts such as M. rivulata and the invasive turtle species Trachemys scripta (Thunberg) [ 19 ] on the other. Therefore, one may wonder whether the haemogregarine distribution is correlated to that of its definitive host, namely the Placobdella leech.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While levels of COI genetic variations clearly indicate the occurrence of several haemogregarine species within the same host species in sympatry, even in syntopy, which is illustrated by numerous cases of coinfections, it is still extremely difficult to link a particular molecular lineage to a specific morphological species, as also reported in [ 17 ]. While the first molecular investigations on Haemogregarina have shown from nuclear markers that H. stepanowi possesses a wide distribution though Europe, Turkey, and the Middle East to Iran with a very low host-specificity [ 12 ], the most recent advents in molecular systematics of H. stepanowi have shown that this species could be actually split into a great number of distinct cryptic haemogregarine species [ 15 , 19 , 52 , 53 ], infecting E. orbicularis and M. leprosa on the one hand and additional hosts such as M. rivulata and the invasive turtle species Trachemys scripta (Thunberg) [ 19 ] on the other. Therefore, one may wonder whether the haemogregarine distribution is correlated to that of its definitive host, namely the Placobdella leech.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low host specificity of H. stepanowi against its intermediate host on the one hand [ 12 , 13 , 14 ] and the high diversity of Haemogregarina spp. in certain turtle species on the other [ 16 , 17 , 18 , 19 ], the host specificity of Haemogregarina could act against leeches—namely Placobdella as the definitive host—as claimed earlier by Attia El Hili et al [ 16 ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Molecular phylogenies have been based on nuclear, mitochondrial, and apicoplast DNA sequences [23]. The most recently published data indicate the presence of different lineages of Haemogregarinae in E. orbicularis obtained from seven different localities in Serbia and North Macedonia [24]. However, all animals monitored in our investigation were derived from the same natural habitat, and they were kept in the same pond in the quarantine section of Belgrade Zoo, which could explain the detection of the amplifications of 18S rRNA sequence in all 31 positive animals.…”
Section: Discussionmentioning
confidence: 99%